Shariah-related information disclosure and characteristics of enterprise among SMEs in Malaysia - Noor Azman, Ain Farahin; Mahat, Fauziah; Mat Daud, Zaidi; Mohd Said, Ridzwana (2019)
Introduction: In Malaysia, SMEs are the potential and future growth to the economy of the country. However, they have not been given enough attention as the various researchers have been biased towards larger and listed enterprises in Malaysia.Objective: to examine the extensiveness of Shariah-related information disclosure among SMEs in Malaysia and to evaluate the relationship between Shariah-related information disclosure and Performance of SMEs. Methods: The study involved a self-developed questionnaire that was personally distributed to employees.In total, 150 questionnaires were distributed and 120 employees who work in various positions in different types of industries from North and East Malaysia participated as respondents of this study.